Anti-chromatin antibodies in systemic lupus erythematosus: a useful marker for lupus nephropathy. Issue 5 (1st May 2003) - Cervera, R; Viñas, O; Ramos-Casals, M; Font, J; García-Carrasco, M; Sisó, A; Ramírez, F; Machuca, Y; Vives, J; Ingelmo, M; Burlingame, R W
Abstract : Background: Anti-chromatin antibodies have recently been described in patients with systemic lupus erythematosus (SLE) and it has been suggested that their presence is associated with lupus nephritis. Objective: To assess the prevalence and clinical associations of these antibodies in SLE. Methods: The presence of anti-chromatin antibodies in 100 patients with SLE was investigated by an enzyme linked immunosorbent assay (ELISA). To determine the specificity of these antibodies, 100 patients with primary Sjögren's syndrome, 30 with primary antiphospholipid syndrome (APS), 10 with systemic sclerosis, and 100 normal controls were also tested. Results: Positive levels were detected in 69/100 (69%) patients with SLE. In contrast, they were found in only 8/100 (8%) of those with primary Sjögren's syndrome, in 1/10 (10%) with systemic sclerosis, in 2/30 (7%) with primary APS, and in none of the 100 healthy controls. Patients with anti-chromatin antibodies had a twofold higher prevalence of lupus nephropathy than those without these antibodies (58% v 29%, p<0.01). A significant correlation was found between the levels of anti-chromatin antibodies and disease activity score as measured by the European Consensus Lupus Activity Measurement (ECLAM; p=0.011). Conclusions: The measurement of anti-chromatin antibodies appears to be a useful addition to the laboratory tests that can help in the diagnosis and treatment of SLE. These antibodies are both sensitive and specific for SLE, and are a useful marker for an increased risk of lupus nephritis.